TYROSINASE INHIBITION, 2,2-DIPHENYL-1-PICRYLHYDRAZYL RADICAL SCAVENGING ACTIVITY, AND PHYTOCHEMICAL SCREENING OF FRACTIONS AND ETHANOL EXTRACT FROM LEAVES AND STEM BARK OF MATOA (POMETIA PINNATA) - Sauriasari, Rani; Azizah, Nur; Basah, Katrin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study aims to investigate the potency of matoa as a tyrosinase inhibitor and antioxidant and also to identify the chemical compounds in the most active fraction and an ethanol extract from the leaves and stem bark of matoa. Methods: The extracts were tested for their tyrosinase inhibitory activity by evaluating the formation of L-dopachrome at 490 nm. Antioxidant activity was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The most active extract from liquid-liquid partition analysis was fractionated, and then, the assays were performed. Results: The ethanol extract of leaves and stem bark of matoa showed weak anti-tyrosinase activity (percent inhibition was 24.54Â±0.22% and 21.93Â±0.57%, respectively, final concentration 200 Î¼g/mL), but they showed strong DPPH radical scavenging activity (IC50 values were 6.11 Î¼g/mL and 5.47 Î¼g/mL, respectively). The ethyl acetate fraction was the most active fraction with an IC50 value of 5.38 Î¼g/mL. Ethanol extract from the leaves and stem bark of matoa and the ethyl acetate fraction contains flavonoids, tannins, saponins, triterpenoids, and glycosides. Conclusion: Matoa does not have potency as a tyrosinase inhibitor, but it has good antioxidant activity, although still lower than that of quercetin.